Forecasting load demand using artificial neural network (ANN) / Alias Khamis - Khamis, Alias (2002)
Recently, Artificial Neural Network is widely used in intelligent computational technology for data compression, pattern recognition and machine learning. This paper presents the development of artificial neural network (ANN) using Back-propagation to forecast the load demand at Maintenance Building at UiTM Shah Alam campus. The data is taken from the Maintenance Department that has installed remote metering system. The programme was developed using Borland C++ version 5.02.